The Effectiveness of Mindfulness-based Therapy on Mental Strength and Self-Coherence in students - Erfani jazzi, Maryam; Mohajer Ghaderabadi, Mahnaz; Ameriyan, Mohammad (Iranian Journal of Neurodevelopmental Disorders, 2023)
Introduction and purpose: improving the personality characteristics of students, including mental strength and self-coherence, is the subject of attention of psychologists and psychotherapists; Therefore, the current research was conducted with the aim of determining the effectiveness of mindfulness-based therapy on mental strength and self-coherence in students. Methods: The current research was a semi-experimental pre-test-post-test type with a control group. The research population included all the male students of the sixth grade of elementary school in Semnan district in the academic year of 2021-2022, and 30 eligible people were selected by available sampling method and randomly placed in two control and experimental groups (15 people in each group). The experimental group participated in eight mindfulness sessions, but the experimental group did not receive training. For the pre-test and post-test, the mental strength questionnaire of Clough et al. (2002) and sense of coherence of Felstenberg et al. (2006) were used. Findings: The results of univariate covariance analysis showed that there is a significant difference in the scores of mental strength and self-coherence between the experimental and control groups in the post-test. Conclusion: The application of mindfulness-based therapy improved the mental strength and self-coherence of students, so the use of mindfulness therapy as a complementary educational therapy in schools is suggested to improve the health of students.